2008
DOI: 10.1111/j.1365-2567.2007.02734.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator activated receptor γ is not necessary for the development of LPS‐induced tolerance in macrophages

Abstract: SummaryPeroxisome proliferator activated receptor-c (PPARc) has been reported to exert anti-inflammatory properties in endotoxic shock and sepsis. One phenomenon that alters the inflammatory response to endotoxin [lipopolysaccharide (LPS)] is endotoxin tolerance, which is caused by previous exposure to endotoxin. Here, we investigate whether changes in endogenous PPARc function regulate this phenomenon using three different models of LPS-induced tolerance in macrophages. In a first in vitro model, previous LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…1d, e). Here, our finding of ET in cultured peritoneal macrophages is consistent with previous studies (Kraatz et al, 1998; Zingarelli et al, 2008). Despite obvious differences in the turnover rate and antigen presentation, microglia share many similarities with macrophages (e.g.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1d, e). Here, our finding of ET in cultured peritoneal macrophages is consistent with previous studies (Kraatz et al, 1998; Zingarelli et al, 2008). Despite obvious differences in the turnover rate and antigen presentation, microglia share many similarities with macrophages (e.g.…”
Section: Resultssupporting
confidence: 94%
“…We found isolated peripheral macrophages formed tolerance when exposed to repeat LPS challenges (Fig. 1), which is consistent with reported studies (Kraatz et al, 1998; Zingarelli et al, 2008); however, enriched microglia failed to form ET (Fig. 1).…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, we found that EPO promoted infection resolution and ameliorated inflammatory response through a ligand-activated transcriptional factor peroxisome proliferator–activated receptor gamma (PPAR-γ) in macrophages ( 19 ). Nevertheless, recent study showed that PPAR-γ is not necessary for the development of LPS tolerance in macrophages ( 46 ). Therefore, we determined to examine other signaling pathways which may play important roles in the re-programming of endotoxin tolerance mediated by EPO.…”
Section: Discussionmentioning
confidence: 99%